Transforming the Kafala in Saudi Arabia: Turning weaknesses into opportunities - Al-Saud, Madawi A (Cranfield University, 2023)
The research sought to find out what is really going on in the modern Kafala and to create solutions for reform based on what is right for Saudi instead of being led by outside voices. The research focuses on migrant domestic workers as one of the most marginalized and vulnerable groups in Saudi, with Kafala practices that amount to modern slavery. The value of this lies in, firstly, promoting the interests of Saudi and the GCC; secondly, upholding human rights and associated principles; thirdly, contributing to an international understanding of Islam and the GCC; and fourthly, providing a culturally specific solution to reforming the Kafala. The selected research methodology consists of mainly qualitative interviews of government officials and other professionals. The research has identified cross-cutting issues that must be addressed by reforms of the Kafala, and that are borne out of the intersecting issues of slavery, Islam, and gender. These cross-cutting issues include: culture (in particular the fact that the status of women and foreigners means that their exploitation may be culturally accepted); migration (which includes the global context of migration and Saudi’s own aims in relation to the system); and access to justice (such as the problem of ensuring that legal reforms are implemented and people are able to exercise their rights).
© Cranfield University 2022. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner.
Keywords: Kafala System; Saudi Arabia, GCC; Migrant workers; Female domestic workers; Islam and gender; People ttrafficking; Slavery